(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Hedging is a linguistic act aimed at reducing assertion force, conveying politeness, and managing difficult conversationalists in electronic communication, particularly in the Iraqi dialect. The study explores the use of hedging strategies in Iraqi Arabic Facebook Reels, focusing on their pragmatic function and sociocultural implications, and identifies similarities and differences between English and Arabic in expressing this concept. The research will use a pragmatic approach to analyse how the Iraqi dialect of Arabic incorporates hedging into daily comments and interactions on short-video sharing platforms like Facebook Reels. The study utilised Facebook Reels and comments as data sources to examine language devices, including modal verbs, conditional phrases, indirect expressions, and culturally specific phrases, which are typically used in the Iraqi dialect of Arabic. To achieve the aim of the study, the research investigates the validity of three hypotheses: 1) Iraqi people use hedging in daily conversations, 2) it influences speakers’ speech on social media, and 3) the speakers’ cultural background influences their hedging. The results showed that hedging serves several functions and purposes in the Iraqi dialect, including decreasing certainty, showing respect, avoiding confrontation, and maintaining social order or balance. The study recommends that hedging is a valuable communication tool in Iraqi society, reflecting cultural and social norms. It shows how Iraqi Arabic is changing in the digital world, where culturally significant actions mix with modern language usage, demonstrating how important it is to be careful when communicating.